2017
DOI: 10.1007/s00280-016-3232-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gefitinib efficacy according to body mass index, body surface area, and body weight in patients with EGFR-mutated advanced non-small cell lung cancer

Abstract: PurposeIn patients with epidermal growth factor receptor (EGFR)-mutated, advanced, non-small cell lung cancer (NSCLC), common gefitinib-sensitive EGFR mutations that predict a greater response to therapy include the exon 19 deletion and L858R point mutation. The objective of this study was to evaluate whether body surface area (BSA), body weight (BW), and body mass index (BMI) affect gefitinib efficacy in such patients.MethodsThe medical charts of 138 consecutive patients with advanced NSCLC harboring sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…reported that gefitinib efficacy in patients with EGFR-mutated advanced NSCLC did not differ according to BSA, body weight, or BMI. However, OS was higher in patients with both exon 19 deletion and low BSA than in patients without these characteristics 18 . These results suggested that BSA- and body weight-based dose adjustments could affect the treatment with EGFR TKIs.…”
Section: Discussionmentioning
confidence: 82%
“…reported that gefitinib efficacy in patients with EGFR-mutated advanced NSCLC did not differ according to BSA, body weight, or BMI. However, OS was higher in patients with both exon 19 deletion and low BSA than in patients without these characteristics 18 . These results suggested that BSA- and body weight-based dose adjustments could affect the treatment with EGFR TKIs.…”
Section: Discussionmentioning
confidence: 82%
“…Underweight (BMI < 18.5 kg/m 2 ) has been shown as a worse prognostic factor not only in operable patients with early stage of lung cancer [20-22], but also in patients with advanced lung cancer [2, 23]. In contrast, regarding patients with mutant EGFR, BMI has been controversial as a prognostic factor [24-27]. Two Japanese studies of 138 patients treated with gefitinib [24] and of 47 patients with acquired T790M-positive mutation who had been treated with osimertinib after prior EGFR-TKI [25] failed to show any significant differences in response and PFS among underweight, normal weight and overweight patients, and between patients with BMI < 21.5 and those with BMI ≥ 21.5, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, regarding patients with mutant EGFR, BMI has been controversial as a prognostic factor [24-27]. Two Japanese studies of 138 patients treated with gefitinib [24] and of 47 patients with acquired T790M-positive mutation who had been treated with osimertinib after prior EGFR-TKI [25] failed to show any significant differences in response and PFS among underweight, normal weight and overweight patients, and between patients with BMI < 21.5 and those with BMI ≥ 21.5, respectively. Oppositely, in a Korean study of 95 patients, patients with BMI ≤ 20.8 had a longer PFS than those with BMI > 20.8 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies investigated the impact of other weight-related clinical characteristics such as body mass index (BMI), body surface area (BSA), and body weight (BW) at diagnosis on survival for EGFR-TKI therapy in EGFR mutant NSCLC patients 18 - 21 . However, the conclusions of these studies about the effects of BMI and BSA on survival were controversial and no predictive value of BW on the efficacy of EGFR-TKI was found.…”
Section: Discussionmentioning
confidence: 99%